Evaluation of Final Project Cost and Time Estimates for the Rehabilitation of The Segiri Sports Hall Building, Samarinda City, Using the Earned Value Method - Afrianto Tandi Renden; Wateno Oetomo; Hanie Teki Tjendani (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2025)
Evaluation of the final project cost and time estimates is essential to measure whether the project can be completed in accordance with the previously established budget and schedule. The calculation of the final cost and time estimates for the rehabilitation project of the Segiri Sports Hall Building in Samarinda City uses the Earned Value Method (EVM). The evaluation is performed by calculating the Estimate At Complete (EAC) for cost projection and the Estimate At Schedule (EAS) for the project completion time estimate. The analysis results show that the EAC experienced fluctuations, starting from Rp 44,648,760,330.58 in the first week of July and increasing to Rp 52,630,845,855.14 in the 15th week of November. This change was influenced by the increase in the Actual Cost of Work Performed (ACWP), which reached Rp 31,173,250,000.00 in the 15th week, as well as a decrease in the Estimate To Complete (ETC), reflecting cost adjustments. Although the EAC showed an upward trend from July to October, there was a decrease in November, indicating an improvement in project cost management. In terms of time, the EAS shows that the project was running ahead of schedule from the first to the third week, with EAS values ranging between 16.57 and 16.41. However, starting from the 4th to the 6th week, the EAS increased significantly, reaching 28.80 in the 6th week, reflecting a delay. Although there was a decrease in the EAS in the 14th and 15th weeks, the project still showed a significant delay compared to the planned schedule. These findings emphasize the importance of further evaluation in time management and resource allocation to minimize delays and ensure the project is completed on target.